Building Child-Friendly Cities for Sustainable Child Development: Child-Friendly City Scale-Child Form - Sapsaglam, Ozkan; Eryilmaz, Ali (MDPI, 2024)
Designing child-friendly cities is very important for sustainable human development. Child-friendly cities encourage children to grow up in a healthy, safe, and supportive environment. The concept of the Child-Friendly City emerged in 1996 at the United Nations Habitat II Conference in Istanbul. This movement promoted supporting children's development, assuring compliance with their basic rights, and pursuing their subjective well-being through the qualities of the environments of cities. Developing measurement tools to determine the effects of the qualities of the city and its environment on children and what is expected from Child-Friendly Cities is crucial. The first aim of this study was to utilize exploratory factor analysis (EFA) to develop the Child-Friendly City Scale-Child Form and provisionally examine its factor structure during this process. The second aim was to examine the factor structure of the developed scale through confirmatory factor analysis (CFA). Participants were 527 middle school students who were divided into two groups for CFA and DFA, 204 in the first group and 323 in the second group. The results of both EFA and CFA supported the developed scale, which has eight dimensions. The Child-Friendly City Scale-Child Form was found to be valid and reliable through various tests. This study contributes to the literature by providing an empirically tested 8-dimension tool to measure children's perceptions of the child-friendliness of their cities.
Keywords: environment; child; sustainability; child friendly city; scale; VIEWS; BENEFITS; Science & Technology - Other Topics; Environmental Sciences & Ecology